The effectiveness of further education and training programs for plastic and aesthetic surgeons: an evaluation according to Kirkpatrick levels 1–3 - Nora A. Hoppmann; E. H. Manassa; L. Kleining; J. P. Ehlers (BMC Medical Education)
Abstract This article examines the success and effectiveness of a further education and training program on wrinkle injections for plastic and aesthetic surgeons using the Kirkpatrick model. Data on course satisfaction, learning progress and the application of what has been learnt in the professional environment were collected using two questionnaires before and after the wrinkle course. Log data from a learning management system is also used. Level 1 - reaction shows a high level of satisfaction with the further education and training program among course participants. Level 2 - learning shows a significant improvement after the wrinkle course when assessing the level of knowledge. Level 3 - behavior shows that the participants successfully apply the newly acquired wrinkle injection skills in their everyday work, especially when injecting with botulinum toxin A. The results of this study show that the Kirkpatrick model helps to measure the effectiveness and success of the offered wrinkle course. Important insights are gained for the design and evaluation of further education and training programs for plastic and aesthetic surgeons.